2019
DOI: 10.1080/08123985.2018.1561147
|View full text |Cite
|
Sign up to set email alerts
|

The initial appraisal of buried DAS system in CO2CRC Otway Project: the comparison of buried standard fibre-optic and helically wound cables using 2D imaging

Abstract: This study aims to assess the ability of shallow Distributed Acoustic Sensing (DAS) to serve as a cost-effective seismic sensor array for permanent monitoring applications. To this end, as part of the CO2CRC seismic monitoring program, a fibre-optic DAS array was deployed alongside a permanently buried geophone array at the Otway Project site (Victoria, Australia).The DAS array consisted of a standard commercially available tactical fibre-optic cable, which was deployed in 0.8 m deep trenches. A custom designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The pronounced directional response of a linear fiber can be alleviated by winding the fiber in a helix around the cable. This increases sensitivity to P seismic waves that are not traveling parallel to the fiber (Kuvshinov, 2016) and field tests confirm this capability (Hornman, 2017;Yavuz et al, 2019). However, a helical winding reduces the sensitivity to S waves (Baird, 2020).…”
mentioning
confidence: 99%
“…The pronounced directional response of a linear fiber can be alleviated by winding the fiber in a helix around the cable. This increases sensitivity to P seismic waves that are not traveling parallel to the fiber (Kuvshinov, 2016) and field tests confirm this capability (Hornman, 2017;Yavuz et al, 2019). However, a helical winding reduces the sensitivity to S waves (Baird, 2020).…”
mentioning
confidence: 99%
“…The approach we used is intended to measure the strain tensor at several locations, instead of measuring strain components distributed at many locations, which is the approach used by other optical fiber strain sensors. This makes distributed strain sensing well suited to measure basic aspects of a transient strain field distributed in space, and applications of distributed strain sensing have capitalized on this aspect by measuring strain distributed at hundreds or more locations along optical fiber in boreholes (Becker et al., 2017; Xue & Hashimoto, 2017), or in networks of trenches (Yavuz et al., 2019). Another limitation to using low frequency to quasi‐static strain tensor data is the need to remove strains caused by earth tides, barometric pressure fluctuations, rainfall, and other processes unrelated to changes in reservoir pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Data from fiber in tubing in fluid-filled boreholes show strong tube wave reverberations. Fiber deployed on casing with a mix of cemented and uncemented zones at the Ketzin, Germany, CO 2 site yielded poorer data quality in uncemented sections than in cemented sections (Daley et al 2013(Daley et al , 2016Egorov et al 2017;Correa et al 2019;Yavuz et al 2019).…”
Section: Exploration-scale Imagingmentioning
confidence: 99%
“…Abbreviations: DAS, distributed acoustic sensing; NRMS, normalized root mean square; OBC3D, 3D Imaging with Ocean Bottom Cable instruments; RMS, root mean square; VSP, vertical seismic profile. (Daley et al 2013, Egorov et al 2017, Correa et al 2019, Yavuz et al 2019). Also at the Otway site, researchers showed that time-lapse full-waveform inversion (FWI) imaging could be used to target a layer just 20 m thick where injection had the greatest effect (Egorov et al 2017).…”
Section: Exploration-scale Imagingmentioning
confidence: 99%